Determinación de la calidad de absorción visual en las unidades de paisajes del páramo Llanganates, laguna de Pisayambo. - Garzón Coello, Ricardo José (2023)
This research project focuses on determining the quality of visual absorption in the landscape units of the Llanganates páramo, Pisayambo Lagoon, located in Santiago de Píllaro canton, Tungurahua province. The objectives were to analyze the current situation of the Llanganates páramo landscape, identify landscape units and visual absorption capacity, and establish a proposal for páramo conservation. The methodology applied in the research is the inductive method, which allows us to determine the most valuable information within the study area. The chosen technique for data collection was photographic records, using the Bureau of Land Management (BLM) 1980 methodology for the evaluation and characterization of the visual quality of the landscape, taking into account aspects such as terrain morphology, vegetation, water, color, and scenic context. Yeomans' methodology (1986) was used to provide evaluation criteria and scoring on aspects such as slope, erodibility, regeneration capacity, vegetation diversity, vegetation/soil contrast, rock/soil contrast, and anthropization. The results obtained indicate the current conditions of the landscape, which is classified as Class A, corresponding to a high-quality landscape with areas of medium fragility and medium regeneration capacity. It can be concluded that the páramo requires conservation efforts in the environmental, economic, cultural, social, and political realms, starting with raising awareness among the population and regulating anthropogenic activities that affect this ecosystem.